The Relationship Between Pregnant Women With Kek and The Birth of Lbw Babies in The Work Area of Bere-Bere Community Health Center - Asriani M. Djauhar; Anik Sri Purwanti; Rifzul Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Background: Low Birth Weight (LBW) is one of the indicators of infant health that is greatly influenced by the nutritional status of the mother during pregnancy. Pregnant women with poor nutritional status have a higher risk of giving birth to babies with low birth weight. This study was conducted to examine the relationship between the nutritional status of pregnant women and the incidence of LBW in the work area of bere-bere community health center  work area. Objective: This study aims to determine the relationship between the nutritional status of pregnant women and the incidence of LBW at the work area of bere-bere community health center  in 2023. Method: This study used an observational analytical design with a cross-sectional approach. The number of respondents was 16 pregnant women selected through a purposive sampling technique. Data were collected by measuring nutritional status using Body Mass Index (BMI) before pregnancy and collecting medical record data on the baby's birth weight. Statistical analysis was performed using the Chi-Square test with a significance level of 0.05. Results: Based on the results of the analysis, it was found that out of 16 respondents, 6 pregnant women (37.5%) with poor nutritional status gave birth to babies with LBW, while 10 pregnant women (62.5%) with normal nutritional status gave birth to babies with normal weight. The results of the statistical test showed a p-value of 0.000 (p < 0.05), which indicated a significant relationship between the nutritional status of pregnant women and the incidence of LBW. Conclusion: There is a significant relationship between the nutritional status of pregnant women and the incidence of LBW. Pregnant women with poor nutritional status have a higher risk of giving birth to babies with LBW. Suggestion: It is recommended that health workers at the work area of bere-bere community health center  be more active in providing education and monitoring the nutritional status of pregnant women through nutritional counseling and regular pregnancy check-ups. Nutrition intervention programs also need to be strengthened to prevent the incidence of LBW